Determinantes da pobreza e dinâmica dos rendimentos nas regiões metropolitanas do Brasil no período de 1995 a 2009 - Carneiro, Douglas Mesquita (2013)
This research aims to study the determinants of poverty and the income dynamics in the metropolitan regions of Brazil from 1995 to 2002 and from 2003 to 2009. It is organized in two essays, using data from the National Household Sample Survey (PNAD). At first, is analyzed the behavior of poverty according to its macrodeterminants, growth and inequality, in the metropolitan regions of Brazil , thereby using the temporal and spatial Shapley decomposition, proposed by Shorrocks (1999). The measurement of poverty was through the family of FGT indices (Foster, Greer and Thorbecke, 1984), using two poverty lines. The results showed small changes in poverty levels in the period 1995-2002, and the inequality component was the main determinant of the observed changes. The following period, 2003-2009, differs from the previous because it presents a declining trend in poverty indicators for all metropolitan areas, the growth component was the main determinant of this trajectory, despite income inequality also declined. As regards the spatial analysis of decomposition of poverty there were changes in the spatial pattern. There were differences in the decreasing levels of poverty between metropolitan areas. In the second essay we investigate the dynamics of income in Brazil in the same periods. Therefore, we use the decomposition of income into permanent and transitory components, proposed by Gottschalk and Moffitt (1994). Given the nature of the database, we built a pseudo panel with cohorts defined from the year of individual birth. The results indicated a transitory component higher in the initial period, accompanied by a drop in income and little change in the index of income inequality. The following period presented a different situation, with the permanent component higher, together with a rise in income and a significant improvement in income distribution.